Pengaruh Model Pembelajaran Talking Stick Dalam Meningkatkan Keterampilan Berbicara Siswa - Nidaul Fitri Hamdani; Riris Nurkholidah Rambe (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2022)
Abstract : The purpose of this study is to identify the impact of the Talking Stick Training form in training the speaking skills of teaching children. This investigation was tried at MIN 04 Labuhanbatu Utara Regency, the subjects of this observation are 4th grade elementary school students, plus 2 classes, special class A and class B, each class contains 18 students, class A runs as Analytical without stopping class B being the Control class. This review is shown with a quantitative research form of trial type. Accumulating data in this statement using Perception and Test sheets. The side effects of this study must be seen from the example t- Test table which reports that the need figure is 0, 000 on the basis of 0, 05. Ho is rejected as well as Ha is recognized, as well as that actually means there is a great effect of the Talking Stick learning form in training students' speaking skills. Therefore, it is recommended for teachers and prospective teachers to use learning forms that are suitable for the learning objectives, one of which is the Talking Stick learning model which can affect students' speaking skills.